Modelling with natural material for teaching pottery in lower secondary school / Zaiyana Mahbib - Mahbib, Zaiyana (2013)
The main outcome of this thesis is to promote the use of natural clay for teaching pottery in lower secondary school. The researcher used the experimental studies basis in producing and utilizing natural clay as a main medium of teaching aids in pottery. As a response to art teachers’ reluctance to practice natural clay in modeling activity due to certain problems, the researcher had delineated research questions and observation on clay works in order to increase the interest among art teachers based on the findings. The preparation process of self dug clay and hand building techniques which has been experimented and compiled is to provide as guidance to visual art teachers or layman who wants to begins and producing pottery in school. This thesis will also be able to change the mindset and perception of the art intellectual towards this versatile material by introducing the uniqueness and exceptional about the genuinely of the clay. The malleable and pliable characteristics found in this material is suitable for artistic expression, also very user friendly and ease to handle by all ages in producing creative stuffs. The researcher hopes that the findings of this research may increase the interest and change the pattern of teaching and learning of the Visual Art Education subject among art teachers. The findings of this research can also lead to a fun clay learning and creative teaching pottery activity which can be practiced not only in schools, but by public as a common art activity.